Saccharide-originated fluorescent carbon dots synthesized by in-liquid plasma with controlled orderliness of carbon core through precursor alteration for selective and rapid metal ion detection - Treepet S. (2023)
Carbon dots (CDs) have grown interested in replacing metal-based quantum dots due to their fluorescent properties with low toxicity. The green synthesis, therefore, represents a contribution to this research field. Here, we demonstrate the synthesis of CDs from simple saccharides, including fructose, glucose, and sucrose, using an eco-friendly method—solution plasma (SP)—by applying plasma in the aqueous solution of the precursor. Variations and characterizations are conducted to understand the role or influence of each synthesis parameter, i.e. saccharide precursor's molecular structure, solution pH (2, 5, and 8), and post-treatment method (freeze-drying and heat-drying), in the materials' structure and fluorescent properties. Blue light-emitting CDs are prepared from all precursors of pH 5 and 8 through SP, followed by heat-drying. Results show that SP is responsible for the carbon core formation, and thus the precursor type affects the carbon core's orderliness. Heat-drying causes oxidation on the CDs' surface, whereby OH functional groups change to C=O. Among all samples, the CDs synthesized from fructose at pH 5 (Fru-CDs-5) perform the best photoluminescence property, having the highest quantum yield (QY) of 9.16% and exhibiting an outstanding ability to detect Fe3+ ions. This is the first attempt to evince the potential use of SP to synthesize CDs from natural carbon sources and obtain CDs exhibiting superior fluorescence properties without any doping and complex synthesis steps. In addition to offering a new synthetic approach, this work specifies the role of the SP and the effect of the saccharide's molecular structure, which is the most relevant synthesis parameters mandatory to obtain tailored CDs with precise control.